Advances in physical ergonomics and human factors - Goonetilleke, Ravindra S.; International Conference on Physical Ergonomics and Human Factors (2019 : Washington, D.C.); Goonetilleke, Ravindra S.; Karwowski, Waldemar, 1953-; Ohio Library and Information Network; International Conference on Applied Human Factors and Ergonomics 2019 : Washington, D.C) (Cham, Switzerland : Springer, 2020)
This book reports on the state of the art in physical ergonomics and addresses the design of products, processes, services, and work systems to ensure they are productive, safe, and enjoyable for people to use. The human bodys responses to physical and physiological work demands, strain injuries from repetition, vibration, force, and posture are the most common types of issues examined, along with their design implications. The book explores a wide range of topics in physical ergonomics, including the consequences of repetitive motion, materials handling, workplace safety, the usability of portable devices, design, working postures, and the work environment. Mastering physical ergonomics and safety engineering concepts is fundamental to creating products and systems that people can safely and conveniently use, as well as avoiding stresses and minimizing the risk of accidents. Based on the AHFE 2019 Conference on Physical Ergonomics and Human Factors, held on July 24-28, 2019, in Washington D.C., USA, this book provides readers with a comprehensive perspective on the current challenges in physical ergonomics, which is a critical aspect in the design of any human-centered technological system, and for factors influencing human performance
International conference proceedings
Includes bibliographical references and index
Keywords: Human engineering -- Congresses; Electronic books; Conference papers and proceedings; Conference papers and proceedings